Determination of Restaurant Tax Revenue Targets (Case Study in Sumedang Regency) - Rd. Tatan Jaka TRESNAJAYA; Supriyadi SUPRIYADI; Nina SABNITA (PT Keberlanjutan Strategis Indonesia, 2024)
Regional autonomy grants local governments the authority to manage administrative and financial affairs, enabling the optimization of regional revenue, particularly through Regional Original Income (PAD). A key contributor to PAD is regional taxes, including restaurant taxes. The enactment of Law Number 1 of 2022 on Financial Relations between Central and Regional Governments (HKPD) has reshaped tax collection practices, mandating alignment with the law. This study examines the case of Sumedang Regency, a district in West Java, Indonesia. This district has successfully leveraged its geographical and economic potential to exceed restaurant tax revenue targets from 2019 to 2023despite fluctuations caused by the COVID-19 pandemic. Utilizing a mixed-method approach, this research combines qualitative and quantitative analyses to explore factors influencing restaurant tax revenue, such as GRDP, tourist visits, population, number of restaurants, national inflation rate, and BI rate. The findings reveal the need for a comprehensive strategy integrating tax revenue with cross-sectoral development policies. A